2012
DOI: 10.1097/iae.0b013e318214d094
|View full text |Cite
|
Sign up to set email alerts
|

Axial Length Increases and Related Changes in Highly Myopic Normal Eyes With Myopic Complications in Fellow Eyes

Abstract: Our results indicate that the AL can increase significantly in highly myopic normal adult eyes during a 1-year interval, and the increase in the posterior staphyloma height is the most likely cause for the increased AL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 31 publications
2
34
2
2
Order By: Relevance
“…Our earlier report showed that the progression of axial elongation was most significantly associated with superior RPE curvature. 38 Ikuno et al 34 reported that the nasal posterior staphyloma height was significantly greater in eyes with a mCNV than in eyes without a mCNV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our earlier report showed that the progression of axial elongation was most significantly associated with superior RPE curvature. 38 Ikuno et al 34 reported that the nasal posterior staphyloma height was significantly greater in eyes with a mCNV than in eyes without a mCNV.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30][31][32][33][34][35][36][37] In our earlier study on the choroid of highly myopic eyes, we detected a thinner sclera by spectraldomain OCT because both the retina and choroid were very thin. 38 This meant that we should be able to investigate the morphology of the sclera in highly myopic eyes.…”
Section: Introductionmentioning
confidence: 99%
“…Histological studies show that, in the area of the crescent, there is either partial or complete absence of the choroid, Bruch's membrane, and the RPE [3]. In our earlier study, we showed that an increase in the height of the posterior staphyloma in highly myopic healthy adult eyes with myopic complications in the fellow eyes was the most likely cause of the increase in the axial length [4]. The results also suggest that there might be an increase in the size of the peripapillary crescent as the axial length increased.…”
Section: Introductionmentioning
confidence: 98%
“…Such complications are typically caused by excessive elongation of the eyeball, which may also cause decreased choroidal thickness (CT) compared with emmetropic eyes (EE) (4,5) . Until recently, the utility of in vivo choroidal imaging was considered relatively poor.…”
Section: Introductionmentioning
confidence: 99%